Awareness of the Importance of Children's Education in the Small Island Fisherman Community (Case Study of Liukang Loe Island) - Nismawati, Nismawati; Oruh, Shermina; Kamaruddin, Syamsu A.; Agustang, Andi; Wirda, Mona Adria (Universitas Negeri Medan, 2023)
Residents of small island villages are typically classified as low-educated. This study used Liukang Loe Island as a case study to learn the truth about children's education in small island settlements. This study aims to determine how the fishing community understands the importance of education and how to increase public awareness about children's education on Liukang Loe Island. This study, which uses a descriptive qualitative technique with research informants, focuses on the